2021
DOI: 10.1111/xen.12666
|View full text |Cite
|
Sign up to set email alerts
|

Multipotent mesenchymal stromal cells derived from porcine exocrine pancreas improve insulin secretion from juvenile porcine islet cell clusters

Abstract: Neonatal and juvenile porcine islet cell clusters (ICC) present an unlimited source for islet xenotransplantation to treat type 1 diabetes patients. We isolated ICC from pancreata of 14 days old juvenile piglets and characterized their maturation by immunofluorescence and insulin secretion assays. Multipotent mesenchymal stromal cells derived from exocrine tissue of same pancreata (pMSC) were characterized for their differentiation potential and ability to sustain ICC insulin secretion in vitro and in vivo. Is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 60 publications
0
9
0
Order By: Relevance
“…Co-encapsulation studies using islets versus islets and MSC also showed beneficial effects on islet function (64)(65)(66). Intraperitoneally syngeneic transplantation of co-encapsulated islets and MSCs showed significantly lower glycaemia compared to islets encapsulated alone.…”
Section: Co-transplantation Of Islets With Mscs From Different Sourcesmentioning
confidence: 97%
See 2 more Smart Citations
“…Co-encapsulation studies using islets versus islets and MSC also showed beneficial effects on islet function (64)(65)(66). Intraperitoneally syngeneic transplantation of co-encapsulated islets and MSCs showed significantly lower glycaemia compared to islets encapsulated alone.…”
Section: Co-transplantation Of Islets With Mscs From Different Sourcesmentioning
confidence: 97%
“…It is known that Notch1 downregulates the expression of several genes and transcription factors implicated in the development of endocrine cells and insulin ( 72 , 74 ). Juvenile porcine exocrine pancreas-derived MSCs (pMSCs) co-cultured with direct cell to cell contact of juvenile porcine ICCs significantly enhanced beta-cell function, suggesting that cell signaling via adhesion molecules are important ( 57 , 65 ). However, co-encapsulation of such ICCs with pMSCs do not effectively prevent PFO and graft survival was rapidly impaired after transplantation of capsules in immunocompetent mice.…”
Section: Improved Neonatal Porcine Islet Function Survival and Graft ...mentioning
confidence: 99%
See 1 more Smart Citation
“…To determine what role multipotent MSCs may play in graft function, Montanari et al. co‐cultured juvenile porcine islet cell clusters (ICCs) with porcine‐derived multipotent MSCs (pMSCs) both with and without cell–cell contact using the transwell system 42 . They encapsulated ICCs in Ca‐alg microspheres (MS) both with and without pMSCs and transplanted into diabetic and immunocompetent mice.…”
Section: Improving Function Of Porcine Islet Cells For Treatment Of Type 1 Diabetesmentioning
confidence: 99%
“…Another attractive feature of manganese (II) ions is their cross-linking ability triggering polymerization of the alginate. Alginates as bioscaffolds have been used to support transplanted cells [ 12 ]. They are biodegradable, of low immunogenicity, and are injectable [ 13 , 14 , 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%